Spatial characteristics to explain residential photovoltaic adoption intentions: An exploratory analysis - Emily Schulte; Thomas Bruckner; Fabian Scheller (Universität Leipzig, Institut für Infrastruktur und Ressourcenmanagement (IIRM), 2023)
Despite their relevance for adoption levels in spatial analyses, previous studies on adoption intention excluded measures characterizing the living environment of participants such as population density and previous photovoltaic (PV) installations so far. To fill this gap, this study was designed to investigate relations between residential PV adoption intention and characteristics of the living environment of respondents. A quantitative survey was performed on a representative sample of 1,800 homeowners in Germany and matched with registered spatial characteristics on the zip-code level. The Mann-Whitney U test was used to compare the adoption intention between groups with low and high expressions of the independent variables with the total sample, and with consumer segments using the Sinus-Milieu model. The results for the total sample demonstrated that actual PV diffusion, population density, city-type and share of (semi-) detached houses are not significantly related to the individual adoption intention, whereas perceived diffusion is. Two milieu groups showed higher intentions with lower actual PV diffusion in their spatial environment, and two groups revealed higher intentions along with relatively higher incomes. Perceived diffusion is only weakly related to actual diffusion levels, implying a gap between reality and perceptions. Overall, the results imply that spatial characteristics on the zip-code level are not related to individual adoption intention, whereas the perceived presence of PV systems in the social and spatial environment positively influences adoption intention.
Keywords: 330